Patterns of Help‐Seeking Behavior Among Victims of Teen Dating Violence and Abuse: Variations Among Boys and Girls. (15th August 2019) - Lachman, Pamela; Zweig, Janine; Dank, Meredith; Yahner, Jennifer
ABSTRACT: BACKGROUND: Despite the extensive research on rates of teen dating violence and abuse and its' consequences, less is known about help‐seeking behaviors among victims. The goals of this study were to document patterns of help‐seeking behaviors among teen victims of dating violence and abuse and examine sex differences related to such patterns. METHODS: The study involved cross‐sectional surveys of 3745 dating youth from 10 middle and high schools in the northeastern United States, 59% of whom reported some kind of dating abuse victimization. We examined the characteristics of youth who reported any type of dating abuse victimization comparing youth who reported seeking help to youth who did not report seeking help following their victimization. RESULTS: Only 9% of victims reported seeking help after their victimization experience. Help‐seeking differed significantly by sex; female victims were more likely to seek help than male victims, and the types of dating abuse that help‐seekers experienced also varied by sex. Overall, 17% of youth sought help from school counselors and 13% sought help from teachers. CONCLUSIONS: Results suggest that help‐seeking behavior is very uncommon among victim populations, particularly if they are not part of specific dating violence prevention programs. In addition, we found female victims were nearly 2 times more likely to seek help than male victims. Given that few youth seek help on their own, schools might create more formalized reporting mechanisms to ensure such violence is addressed effectively and efficiently, and create peer and parental support networks to build awareness and create comfort for victims.